Critical Role of E1623 Residue in S3-S4 Loop of Nav1.1 Channel and Correlation Between Nature of Substitution and Functional Alteration - Su, Tao; Chen, Meng-Long; Liu, Li-Hong; Meng, Hen; Tang, Bin; Liu, Xiao-Rong; Liao, Wei-Ping (Frontiers in Molecular Neuroscience, 2022)
Objective: An overwhelming majority of the genetic variants associated with genetic disorders are missense. The association between the nature of substitution and the functional alteration, which is critical in determining the pathogenicity of variants, remains largely unknown. With a novel missense variant (E1623A) identified from two epileptic cases, which occurs in the extracellular S3-S4 loop of Nav1.1, we studied functional changes of all latent mutations at residue E1623, aiming to understand the relationship between substitution nature and functional alteration. Methods: Six latent mutants with amino acid substitutions at E1623 were generated, followed by measurements of their electrophysiological alterations. Different computational analyses were used to parameterize the residue alterations. Results: Structural modeling indicated the E1623 was located in the peripheral region far from the central pore, and contributed to the tight turn of S3-S4 loop. The E1623 residue exhibited low functional tolerance to the substitutions with the most remarkable loss-of-function found in E1623A, including reduced current density, less steady-state availability of activation and inactivation, and slower recovery from fast inactivation. Correlation analysis between electrophysiological parameters and the parameterized physicochemical properties of different residues suggested that hydrophilicity of side-chain at E1623 might be a crucial contributor for voltage-dependent kinetics. However, none of the established algorithms on the physicochemical variations of residues could well predict changes in the channel conductance property indicated by peak current density. Significance: The results established the important role of the extracellular S3-S4 loop in Nav1.1 channel gating and proposed a possible effect of local conformational loop flexibility on channel conductance and kinetics. Site-specific knowledge of protein will be a fundamental task for future bioinformatics.